2007
DOI: 10.1007/s00330-007-0743-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of in-stent coronary restenosis detection with multislice spiral computed tomography: a meta-analysis

Abstract: This study was designed to define the current role of multislice spiral computed tomography (MSCT) for the diagnosis of coronary in-stent restenosis using a meta-analytic process. Restenosis remains a limitation after coronary stent implantation and contributes to a substantial number of coronary re-assessments by conventional invasive coronary angiography (CA). We identified 15 studies (807 patients) evaluating in-stent restenosis by means of both MSCT (>or=16 slices) and conventional CA until February 2007. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 34 publications
0
31
2
Order By: Relevance
“…In a meta-analysis of 15 studies, 1175 intracoronary stent were assessed with the 16 and 64-slice CT scanners, and the average sensitivity and specificity were reported as 84% and 91%, respectively (Hamon et al, 2008). In our study, 33% sensitivity of 16-slice CT angiography is below the sensitivities of other studies but 95% specificity level is comparable to other studies.…”
Section: Discussioncontrasting
confidence: 45%
“…In a meta-analysis of 15 studies, 1175 intracoronary stent were assessed with the 16 and 64-slice CT scanners, and the average sensitivity and specificity were reported as 84% and 91%, respectively (Hamon et al, 2008). In our study, 33% sensitivity of 16-slice CT angiography is below the sensitivities of other studies but 95% specificity level is comparable to other studies.…”
Section: Discussioncontrasting
confidence: 45%
“…Routine follow-up angiography in these patients has not been recommended [1]. Previous studies suggest supporting the clinical indications for 64-slice coronary CTA as a gatekeeper for the exclusion of in-stent restenosis, owing to its high negative predictive value [2][3][4][5][6][7]. However, the substantial numbers of unassessable stents, up to 14% [3], limit the usefulness of this approach.…”
Section: Introductionmentioning
confidence: 98%
“…Factors affecting metal artifacts include stent material, stent diameter, strut thickness, and strut design. In fact, small stent diameter has been identified by several groups as a major factor in the failure of in-stent restenosis assessment, with a consensus that only stents with a diameter greater than 3 mm are routinely interpretable in coronary CTA [2]. Schuijf et al showed that images of 41% of stents with thick struts (0.14 mm or larger) were uninterpretable, as compared with images of 11% of stents with thinner struts [3].…”
Section: Introductionmentioning
confidence: 98%
“…With increased number of slice such as 16-and 64-slice scanners, improved diagnostic accuracy has been reported in imaging of coronary artery disease and coronary stents [8-12, 17, 18]. This has been confirmed by a number of systematic reviews or meta-analyses of diagnostic accuracy of multislice CT angiography for detection of coronary in-stent restenosis [19][20][21][22]. It is evident from these reports that MSCT is increasingly playing an important role in the follow-up of patients treated with coronary stents and serves as an effective less-invasive technique.…”
Section: Discussionmentioning
confidence: 72%